Column-anchored zeroforcing blind equalization for multiuser wireless FIR channels. - Jie Zhu
We propose a direct blind zeroforcing approach to cancel intersymbol interference (ISI) in multiple user finite impulse response (FIR) channels. By selectively anchoring columns of the channel convolution matrix, we present two column-anchored zeroforcing equalizers (CAZE), one without output delay and one with a chosen delay. Unlike many known blind identification algorithms, these equalizers do not need an accurate estimate of the channel orders. Exploiting second-order statistics (SOS) of the received signals, they can retain preselected d columns in the channel convolution matrix (d is the number of users) and force the remaining columns to zero. CAZE can effectively equalize single-input-multiple-output (SIMO) systems and can reduce dynamic multiple-input-multiple-output (MIMO) systems into a memoryless signal mixing system for source separation. Simulation results show that the CAZE is not only effective for blind equalization of linear quadrature amplitude modulation (QAM) systems, but it is also applicable to the nonlinear GMSK modulation in the popular wireless GSM systems when computational cost severely limits the use of nonlinear methods such as the Viterbi algorithm
Keywords: FIR channels; ISI cancellation; QAM; SIMO systems; Viterbi algorithm; Blind identification algorithms; Channel convolution matrix; Channel orders; Column-anchored zeroforcing blind equalization; Computational cost; Direct blind zeroforcing; Dynamic MIMO systems; Finite impulse response; Intersymbol interference; Linear quadrature amplitude modulation; Memoryless signal mixing system; Multipath channel; Multiple-input-multiple-output.; Multiuser wireless FIR channels; Nonlinear GMSK modulation; Output delay; Received signals; Second-order statistics; Simulation results; Single-input-multiple-output.; Source separation; Wireless GSM systems